(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In this era of globalisation, both men and women have come to grips with the fact that womenare cognitively and physically inferior to men. This is something that has been brought up inconversations about the many roles that women hold in India. Indians have a long history of honouringfemale deities as goddesses. In spite of the fact that, with very few exceptions, women have beensubjected to patriarchal tyranny from a number of angles from the beginning of time, feminists continueto make their voices known. As a consequence of this, they have been subjected to a wide range ofchallenges, such as being subjected to domination, exploitation, marginalisation, discrimination basedon opportunities, harsh treatment, and isolation from the bulk of human existence. Over the course ofthe last several years, a number of women have established themselves as key contributors to the Indiangovernment. These women have held positions such as president, prime minister, head of bank,speaker, and lieutenant general. On the other hand, women in Indian society have a long history of beingrepressed and excluded from all fields of power. This includes, but is not limited to, the following areasof influence economics, social life, geography, culture, religion, and even their own voices. As aconsequence of this, their predicament is far more terrible and inhumane than that of males. Ever fromthe dawn of time, upper caste women and patriarchal society have reigned over and subjugated them, asMulk Raj Anand demonstrates in his essay titled Untouchable. Mulk Raj Anand’s novel Untouchable isthe subject of this research, which studies passages from the novel and finds parallels to Indianfeminism.